Modernisation of DC-DC converter topologies for solar energy harvesting applications: A review - Tole Sutikno; Hendril Satrian Purnama; Rizky Ajie Aprilianto; Awang Jusoh; Nuryono Satya Widodo; Budi Santosa (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Solar photovoltaic (PV) power generation has become increasingly important as a renewable source of energy due to the many benefits it offers. These benefits include the ease with which it can be allocated; the absence of noise; the longer life; the absence of pollution; the shorter amount of time required for installation; the high mobility and portability of its parts; and the capability of its output power to meet peak load requirements. DC-DC converters are typically incorporated into solar energy harvesting systems because they allow for the more efficient exploitation of solar cells. One of the difficulties is in the selection of a suitable converter since this has an effect on the operation of the PV system. This study discusses the modernisation of several different DC-DC converter topologies for solar energy harvesting systems. Some of these topologies are boost, buck-boost, single-ended primary-inductance converter (SEPIC), Cuk, and flyback. The topologies have been compared so that detailed information on the complexity of the hardware, the cost of implementation, the efficiency of the energy transfer elements, the tracking efficiency, and the efficiency of the converters can be provided. This paper will be useful as a handy reference in choosing the best converter topology for solar energy harvesting applications.